Adult hobby musicians, well-being and motivation : a qualitative survey - Kauppi, Anu (2024)
The aim of this research was to investigate what kind of well-being effects leisure time music making might have on adult hobby musicians and whether there can be found some connections between these well-being effects and motivation. Interest is in the themes which arise from peoples’ self-reflection, aiming to recognize the ways people interpret the importance of the well-being experiences affecting their commitment and motivations. Life-expectancy overall increases, which makes maintaining of the well-being in older ages progressively valuable issue. The research of active adult music participation and well-being has been substantially growing in the past few decades and the results endorse the link between those two This study focuses on how the music is perceived to connect with well-being and how it affects the motivation, aiming to offer wider perspective, build basis for future research and possibly offer encouragement to participate to the activities. Theoretical framework includes concepts of health and well-being and how music is researched to impact these. Also, some information about music making as a hobby, definitions of hobby musicians and some previous knowledge about the motivation are included. Ten adults aged between 30-75 years from United Kingdom participated the study. Answers were collected via internet survey consisting of open-ended questions focusing on the reasons for music making. The method for analysis was inductive thematic analysis, which was done with the assist of ATLAS.ti software. Based on the analysis, music making contributed positively to the overall well-being and health by affecting social, psychological and physical aspects of well-being, each including multiple sub-themes to describe the aspects found in the data. Music making was reported being important part of the well-being and all the participants found activity contributing to various aspects of well-being at the same time, varying from coping with issues faced and increasing the enjoyment of everyday life. The connection to motivation was found to be two-dimensional, highlighting similar themes but whether the effects were negative or positive, were strongly dependant on the person and situation. Results support the previous findings that music can promote better overall well-being, and that the well-being aspects are perceived as important motivational factor to be committed to the music making activity among adult hobby musicians.